A Study of Microbiological Profile in patients with Acute Pyelonephritis in a Tertiary Care Hospital, Nandyal - Pogula Nagarjuna Reddy (Perspectives In Medical Research, 2020)
Background : Acute pyelonephritis is a bacterial infection that affects the renal parenchyma that can be life-threatening and often leads to renal scarring. It usually ascended from the lower urinary tract, and also reach the kidney via the bloodstream. Early diagnosis and management of acute pyelonephritis have a better impact on patient outcomes. Acute pyelonephritis is one of the severe conditions with high mortality and morbidity. It represents the most severe form of urinary tract infection. Acute pyelonephritis is the most common cause of communityonset bacteremia in elderly patients1. Aim: To study the microbiological profile in patients with acute pyelonephritis admitted in a tertiary care hospital. Materials and Methods: A Hospital-based Prospective study was conducted in the Department of Medicine, Santhiram medical college & general hospital for a 2 year period.Universal Sampling Technique was used for the selection of study subjects.The study population included patients admitted with fever, flank pain, and positive urine or blood cultures in the department of general medicine in Santhiram medical college and general hospital.The final sample size was 50 subjects. Results: In the present study, 50 participants were selected as the study population. The mean age of the study population was 57.48 ± 11.21. The majority of participants (70%) were distributed in a 50 to 69-year age group. Majority of participants were females (60%) and males (40%).In the current study among participants, in the current study, urine culture was positive in 29 patients (58%) of the study population. In 29(58%) of the subjects who had a culture-positive infection, the most predominant infectious agent in the present study group was Escherichia. coli and was reported in 22 (44%) of the study subjects. Other causative organisms include, Klebsiella pneumonia was reported in 2(4%) subjects. Candida albicans, Citrobacter, Enterococcus faecalis, and Pseudomonas were isolated in 1 (2%) subject each. One subject had a dual infection with Escherichia coli and Candida.In current study, among the 29 culture isolates, none of them were resistant to Cefperazone plus Sulbactum or Piperacillin plus tazobactam. The highest proportion of resistance was reported for Ampicillin as 82.1% of isolates were resistant. Levofloxacin resistance was found in 67.9% of isolates. Gentamicin and Amikacin resistance was found 17.86% and 3.6% of the isolates. Nitrofurantoin resistance was found in 2 (7.1%) of isolates. Conclusion: The mean age of the study population was 57.480 ± 11.2072 years in the study population, and there was a slight female preponderance in the occurrence of APN.The majority of participants (78%) were distributed ina 50 to 69-year age group.Diabetes, hypertension, ureteric calculus, and past history of UTI were the common risk factors identified in the study population.In.More than half (58%) of the study population had a culture-positiveinfection.TheThe most common organism isolated in the study population was E.Coli, responsible for 44% of the cases. None of them were resistant to Cefoperazone plus Sulbactum or Piperacillin plus tazobactam. The other antimicrobials, which have not shown any resistance, were Meropenem and Colistin.The highest proportion of resistance was reported for Ampicillin in 82.1%, followed by Levofloxacin in 67.9% of isolates. ICU admission rate was higher in culture-positive cases (63.6%), as compared to culture-negative cases (36.4%)None of the study subjects had hospital mortality